The fossil avifauna of the tar seeps Las Breas de San Felipe, Matanzas, Cuba - Suárez, William (Zootaxa, 2020)
The Cuban fossil avifauna, prior to this study, included 30 extinct and extirpated valid taxa. In the present contribution, we review the fossil avifauna from Las Breas de San Felipe, and in so doing increase the diversity of Cuban fossil birds to 36 species with the description of a New World vulture, Coragyps seductus sp. nov., three accipitrids, Gigantohierax itchei sp. nov., Buteogallus royi sp. nov., and Buteo sanfelipensis sp. nov., a small caracara, Milvago diazfrancoi sp. nov., plus Buteogallus cf. B. fragilis (L. Miller, 1911), which is recorded for the first time in Cuba and the Antillean Subregion. Of the total of 34 bird species now registered from Las Breas de San Felipe, 21 (61.8 %) are extinct and 13 (38.2 %) correspond to species that still live in Cuba, other Antillean islands, or in the American continent. Raptors dominate the assemblage, with 26 (76.5 %) species. These are mostly from Accipitridae and Falconidae, and 19 (55.9 %) are diurnal and 7 (20.6 %) nocturnal. This abundance of raptors in Las Breas de San Felipe is similar to the composition from other asphalt deposits known from the American continent such as Rancho La Brea. The palaeoavifauna from this locality can be split, according to ecological preferences, into three groups or guilds. Radiocarbon (14C) dates indicate a late Pleistocene age for some of the recovered bird remains, including those of Antigone cubensis (Fischer & Stephan, 1971) comb. nov., Gymnogyps varonai (Arredondo, 1971) and Ornimegalonyx oteroi (Arredondo, 1958).